PERAN MEDIA SOSIAL TERHADAP KUALITAS PELAYANAN PEMBUATAN E-KTP DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Utami, Sayyidah Dutha; D, Herman; Mustanir, Ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to determine the role of social media in the quality of e-KTP preparation services in the Population and Civil Registration Office of the Cidenreng Rappang District. The population of this study is 49, 22 office staff and 27 civilians who served in the Population and Civil Registration Office of Cedenring Rabang District in November 2023. This type of study describes metaphors. The data collection methods used in this study are observation, literature review and questionnaires. The data is used with the help of IBM SPSS Statistics 21.0 application. The results of this study from the results of the questionnaire found that the role of social media exchange was reiterated at 58% in the "negative" category. 58% of service quality falls into the "poor" category. Service level 53.9%, organizational level 22.5%, human resources and skills 15% and 16.4%. Therefore, the role of public media in the quality of KTP electronic services in Cidenreng Rappang Regency Civil Registry Service is still not considered good by the community.